(untitled) (Castilla. Estudios de Literatura, 2024)
This article presents a theoretical-methodological approach to analyse the translation of metaphor, based on the interactions and distinctions between the two phenomena. Analogical thinking, creativity and narrative potential are proposed as characteristics that relate metaphor to translation at micro and macro levels. An ad hoc methodology is proposed, which brings out the relationships between the two phenomena and employs interdisciplinary tools such as corpus construction and analysis. The results obtained can be used to further describe how metaphors are reconceptualised in translated texts